Role of Enterococcus Fecalis in Endodontic Treatment Failure - Anand, Priyanka; Kasarla, Rajeshwar Reddy (Medical Journal of Eastern Nepal, 2024)
Endodontic treatment is generally an effective and safe treatment with a high success rate, but failure may occur in many cases. The main reason for endodontic failure is attributed to the presence of some bacteria inside the root canal system such as Enterococcus faecalis. This article reviews and summarizes the different conditions and attributes that make E.faecalis a potential threat in endodontic treatment failure.